LEARNING STYLES AND TEXTBOOK DESIGN: A CASE STUDY OF 'BAHASA INGGRIS WORK IN PROGRESS' FOR TENTH GRADE - Reynaldi, Kelvin; Refnaldi, Refnaldi (English Review: Journal of English Education, 2024)
Textbooks can provide effectiveness and efficiency in the learning process for both teachers and students. Meanwhile, learning styles are individual or student preferences in processing information, which are generally categorized into visual, auditory, and kinesthetic. Therefore, textbooks should accommodate learning styles in a balanced way for a more efficient and effective learning process. This study aims to analyze the learning styles accommodated by the textbook 'Bahasa Inggris Work in Progress' for grade ten. The approach used was descriptive quantitative, with research instruments developed based on Priyatna's (2013) and Bobbi & Mike's (2015) theories. Data analysis was conducted by three independent analyzers to ensure the accuracy and consistency of the results. The research findings show that this textbook accommodates visual learning styles by 39%, auditory by 31%, and kinesthetic by 30%. This result shows a relatively balanced distribution in supporting the three types of learning styles. This research highlights the importance of diversifying teaching methods in textbooks to create an inclusive and effective learning environment. As such, it makes a meaningful contribution to the development of textbooks and teaching strategies that are more responsive to students' learning needs.